Assessing Losses of Power and Electrical Energy in Unbalanced Medium Voltage Distribution Networks - Toader C.; Golovanov N.; Porumb R.; Trishtiu I.; Bulac C.; Mandish Al.; Tirsu M. (Problems of the Regional Energetics)
The work is dedicated to calculating electricity losses related to power lines average voltage overhead or underground, which in terms of construction can be three-phase (three or four wire) in unbalanced sinusoidal harmonic, determining energy efficiency indicators (such as positive and negative factors of unbalance) thereof. It examines a case study and argues the results.